Franco Frabboni tra impegno politico e responsabilità pedagogica - Pinto Minerva, Franca (Studi sulla Formazione/Open Journal of Education, 2011)
The author reinterprets the work and the pedagogical action of Frabboni according to an utopian and political optical and emphasizing the capabilities of Bologna’s intellectual to tie the theoretical with the idea of training. According Frabboni, the risk is determined and the denial of fundamental characteristics of the subject-person, a person who has the right to care and sociality. The school is much in this direction, but a secular public school and who has at heart the fate of all citizens. These are favorite themes in the search of Frabboni and the author proposes a critical reading of these issues.